Methane release effects on foraminiferal tests in northern South China Sea - Cen, Yue; Wang, Jiasheng; Algeo, Thomas J.; Wang, Zhou; Ma, Xiaochen; Chen, Can (Frontiers in Marine Science, 2023)
Upward diffusing methane in gas hydrate geological systems is consumed in the sediment and water column by a series of biogeochemical reactions, which not only affect living foraminifera but also lead to early diagenetic alteration of buried foraminiferal tests. Previous studies of the impact of methane release events on fossil foraminifera focused mainly on carbon and oxygen isotopes, with little attention given to other geochemical proxies to date. Here, we examine the test wall microstructure and analyze the elemental and stable carbon-oxygen isotopic compositions of buried foraminifera from gas hydrate-bearing sediments at Site GMGS2-16 in the northern South China Sea. Our results show that diagenetic alteration of foraminiferal tests at Site GMGS2-16 is mainly linked to high-Mg calcite overgrowths. Test δ13C covaries negatively with the degree of diagenetic alteration (based on petrographic characteristics) but positively with Mg/Ca ratios. With increasing diagenetic alteration, Ba/Ca, Mn/Ca, Fe/Ca, Mo/Ca, U/Ca, V/Ca, Ni/Ca and Co/Ca also generally increase, but Sr/Ca and Cu/Ca exhibit variable changes. We infer that foraminiferal tests are highly susceptible to alteration by methane-bearing fluids, and that the elemental ratios of diagenetically altered tests are potentially reliable proxies for paleo-methane release events. At Site GMGS2-16, the overall pattern of diagenetic alteration of foraminiferal tests records frequent vertical fluctuations of the sulfate-methane transition zone (SMTZ) caused by variable fluid flux and methane release rates, with two discrete large-scale methane release events having maximum ages of 0.47 ka and 170 ka.